R.G.S. (Bob) Currie, 1921-1987 - Beck, Tom (ARCTIC, 1987)
The following eulogy was delivered by Tom Beck, immediate past chairman of the Arctic Institute's Board, at R.G.S. (Bob) Currie's memorial service, July 16, 1987, at Scarboro United Church, Calgary, Alberta. Tribute is paid to Bob for his 18 years of service as an oilman and for his contribution as past chairman, governor and fellow of the Arctic Institute of North America.